Developing Collaborative-Based Supervision Model Which Accentuates Listening and Responding Skills - Indra Prasetia; Akrim Akrim; Emilda Sulasmi (STAI Hubbulwathan Duri, 2022)
This research aims to develop a collaborative-based supervision model that emphasizes three aspects of (1) listening and responding ability and (2) willingness to listen and respond. The research method used is research and development (R D). The subjects of this study were school supervisors and teachers at junior high schools within the Medan City Education Office. This research was carried out from January to November 2021. The results of this study indicate that the model is feasible based on the results of trials with a limited area, main area and operational area. In addition, this study formulated four teachers’ characteristics, namely lazy teachers, unfocused teachers, narrator teachers and professional teachers. Effective supervision practices for the four teachers’ characteristics are carried out with the approach and behaviour of school supervisors through instructions (for lazy teachers), consultation (for unfocused teachers), participatory (narrator teachers) and delegation (professional teachers). By applying the four strategies and behaviours for teachers’ character development in the practice of supervision, the implementation of supervision will achieve the expected results.